2013 International Conference on Materials for Renewable Energy and Environment 2013
DOI: 10.1109/icmree.2013.6893815
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations on turbulent heat transfer of carbon dioxide in a helically coiled tube

Abstract: Experimental investigations on turbulent heat transfer of carbon dioxide in a helically coiled tube were performed under constant wall heat flux conditions. A computational program was compiled in a helical coordinate system to calculate the inner wall temperatures based on the directly measured outer wall temperatures by thermocouples. It was found that the wall temperatures increased with the increasing heat flux and the decreasing mass flux, while the heat transfer coefficients increased with the increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Yang et al (2021) used the RNG k-ε turbulent model with an enhanced wall function to investigate the mechanisms of deterioration and oscillation of the inner wall temperature during SCW cooling in horizontal tubes with sections of various non-circular shapes. Huang et al (2018) studied the HTCs of SCW and CO 2 in a helical tube using a numerical calculation model, and discovered that the SST k-ω turbulent model agreed well with the experimental results of Wang et al (2014), who demonstrated that the maximum wall temperature was at a certain angle in the circumferential direction under the effects of centrifugal force and buoyancy in the helical tube. Wang et al (2015) studied the applicability of various turbulence models for heat transfer calculations in helical tubes using the experimental data from convective heat transfer of supercritical CO 2 in helical tubes.…”
Section: Introductionmentioning
confidence: 56%
“…Yang et al (2021) used the RNG k-ε turbulent model with an enhanced wall function to investigate the mechanisms of deterioration and oscillation of the inner wall temperature during SCW cooling in horizontal tubes with sections of various non-circular shapes. Huang et al (2018) studied the HTCs of SCW and CO 2 in a helical tube using a numerical calculation model, and discovered that the SST k-ω turbulent model agreed well with the experimental results of Wang et al (2014), who demonstrated that the maximum wall temperature was at a certain angle in the circumferential direction under the effects of centrifugal force and buoyancy in the helical tube. Wang et al (2015) studied the applicability of various turbulence models for heat transfer calculations in helical tubes using the experimental data from convective heat transfer of supercritical CO 2 in helical tubes.…”
Section: Introductionmentioning
confidence: 56%